2021
DOI: 10.5812/zjrms.99405
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis B and C Virus Infections in the Couples Attending a Premarital Screening Program in Zakho City, Kurdistan Region of Iraq

Abstract: Background: Hepatitis B and C virus (HBV and HCV) infections are major global health issues and the leading causes of liver cirrhosis and hepatocellular carcinoma. Objectives: The aim of this study was to investigate the prevalence of HBV and HCV infections in couples attending a premarital screening program in Zakho city, Kurdistan region, Iraq. Methods: This cross-sectional study was carried out in Zakho city, Kurdistan Region of Iraq, between January and October 2019. During this period, 2123 couples were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previously, the vast majority of studies from Iraq recruited blood donors 7,9,15,16 . Careful examination showed that all donors were male.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the vast majority of studies from Iraq recruited blood donors 7,9,15,16 . Careful examination showed that all donors were male.…”
Section: Discussionmentioning
confidence: 99%